Albatrellus shouxiangu (Albatrellaceae, Russuales): a new terrestrial stipitate species from Eastern China - Zhang, Xin; Zhao, Ya-Lin; Li, Ming-Rui; Luo, Kai-Yue; Zhou, Hong-Min; Wu, Fang (Phytotaxa, 2025)
A new species, Albatrellus shouxiangu, is described from eastern China based on morphology and phylogenetic analysis using a combined dataset of ITS + nLSU + tef1-α + rpb1 sequences. Albatrellus shouxiangu is characterized by annual, terrestrial, laterally stipitate basidiomata with saffron pileal surface when juvenile, sulphur-yellow to buff when mature, and white pores when fresh, generative hyphae with simple septa, subglobose, weakly amyloid basidiospores measuring 4.4–5.5 × 3.9–4.8 μm, and growing on ground in Vaccinium forests. Phylogenetic analyses confirm its placement within the genus Albatrellus, forming a distinct lineage closely related to A. cantharellus. The present study enhances the understanding of the diversity of Albatrellus in China.